DIGITAL HABITS OF GENERATION Z – STUDENTS OF SPORTS - Markov Čikić, Ivana; Ivanovski, Aleksandar (Sport - nauka i praksa, 2022)
The new virtual reality of today's society and its interaction with members of the younger population is an increasingly common subject of research. The question is whether and to what extent it is possible to stop the domination of the digital. Is sport an activity that can compete with the new virtual reality and the world of video games? The paper presents online habits and inclinations towards video games of the first-year students of the Belgrade College of Sports and Health, not only qualitatively – in order to examine the time spent on video games and compare it with the time spent on sports and recreation, but also qualitatively, in terms of content – topics that occupy this particular segment of population, talented in sports and sports-oriented, but at the same time digitally-oriented.The paper has demonstrated, on a selected sample of sport-oriented members of Generation Z, some deviations from the digital characteristics of the generation they belong to demographically, the generation in which the use and application of technology is dominant in obtaining any practical information, as well as in communication and entertainment. The sample consisting of students of sports academic courses has demonstrated that a very high percentage of these students practice sports on a regular basis defying the current sedentary lifestyle. Many of them do not belong to the present-day youth subculture – ‘the gamers’ community’, and even those who do belong to the pop culture of computer games prefer sports computer games as their choice of virtual content.
Keywords: Generation Z; sports; video games